The Influence of Experiential Marketing on Consumer Satisfaction and Repurchase Intention at Warung Ayam Penyet Bang Amin - Romi Hamdani Siregar; Pristiyono; M. Irwansyah Hasibuan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Consumer satisfaction is one of the main keys in a business, especially the culinary business. purpose: To determine the effect of experiential marketing on customer satisfaction at Warung Ayam Penyet Bang Amin. To determine the effect of experiential marketing on repeat purchase intention at Warung Ayam Penyet Bang Amin. Methods: The method used in this study is Structural Equation Modeling (SEM) using Partial Least Square (PLS) software. Structural Equation Modeling (SEM) is a set of statistical techniques that allows testing a series of relatively complex relationships that cannot be solved by linear regression equations (Statistical Tests). Results: The experiential marketing variable obtained a T-statistic value of 10.819> 1.96 with a P-value of 0.000. This means that experiential marketing has a significant effect on customer satisfaction, or H1 is accepted, The experiential marketing variable obtained a T-statistic value of 26.283> 1.96 with a P-value of 0.000. This means that experiential marketing has a significant effect on repurchase interest, or H2 is accepted. Implications: In growing a business, efforts to improve experiential marketing need to be carefully considered, in order to increase consumer satisfaction and repurchase interest.